PERBEDAAN HASIL BELAJAR IPA ANTARA PENGGUNAAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) DENGAN METODE CERAMAH PADA MATERI BENDA DAN SIFATNYA SISWA KELAS IV SD GUGUS 5 KECAMATAN PANARUKAN KABUPATEN SITUBONDO SEMESTER GANJIL TAHUN PELAJARA - Sri Wahyuni; Eko Hadi Purwanto (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2017)
This study is based on the problems identified at this time students learn merely received the knowledge of teachers in education generally only use learning methods lecture course, so that in the implementation of teaching and learning activities take place monotonous and make difficult students to receive lessons well so impressed create saturated students in learning so that the effect on student learning outcomes. To solve the problem, researchers conducted the study by applying the learning model Contextuan Teaching and Learning (CTL). Formulation of the problem is How the study results to learn science between learning models using Contextual Teaching and Learning (CTL) with a lecture at the fourth grade students? and What is the difference between the use of learning outcomes IPA learning model Contextual Teaching and Learning (CTL) with a lecture at the fourth grade students ?. This study aims to determine learning outcomes IPA between the use of learning model Contextual Teaching and Learning (CTL) with a lecture in class IV, and to determine differences in learning outcomes IPA between the use of learning model Contextual Teaching and Learning (CTL) with a lecture on students class IV. This study uses quantitative research and the research method used is a quasi-experimental method. This study is the fourth grade students who are in two schools SDN 1 Bun (experimental class) and SDN 2 Bun (control group) using 1 RPP held two meetings. The research instrument in the form of documentation and multiple choice objective test of 40 questions with four possible answers. Data were analyzed using t-test, obtained tarithmetic = 8.42, ttable = 2.01 at α = 0.05 and df = 48. It turns out that tarithmetic= 8.42> ttable = 2.01, we conclude that there are differences in learning outcomes IPA between the use of learning model Contextual teaching and learning (CTL) with a lecture on student learning method fourth grade Cluster 5 Districts Panarukan Situbondo. The learning model Contextual Teaching and Learning (CTL) is more suitable to be applied in the process of school learning model than the lecture approach.